The Importance of Monomeric Anthocyanins in the Definition of Wine Colour Properties - Tang, K.; Liu, T.; Han, Y.; Xu, Y.; Li, J.M. (South African Journal of Enology and Viticulture, 2017)
Monomeric anthocyanins are the main contributor of colour in young red wines. To study the importance of monomeric anthocyanins to the wine colour, 41 wines of Vitis vinifera L. Cabernet Sauvignon, Cabernet Gernischt and Merlot were examined. Seven monomeric anthocyanins were isolated and applied as standards in HPLC analysis. Multiple linear regression (MLR) and partial least squares regression (PLSR) were performed to relate and validate the correlations between the monomeric anthocyanins and CIELab colour parameters. Malvidin-3-O-glucoside (Mv3g) was the most abundant anthocyanin in all tested wines, but not the anthocyanin that showed the highest correlation with the colour parameters evaluated. L*, b* and h were shown to be correlated significantly with mainly the anthocyanins for Cabernet Sauvignon, L* with the anthocyanins for Cabernet Gernischt and h with the anthocyanins for Merlot. MLR and PLSR both successfully predicted the colour from the anthocyanin composition of the wine. Delphinidin-3-glucoside (Dp3g), malvidin-3-O-acetylglucoside (Mv3ac) and Dp3g were the most important monomeric anthocyanins contributing to the prediction of the wine colour of Cabernet Sauvignon, Cabernet Gernischt and Merlot respectively. Different grape varieties had profound influences on the correlation of wine colour with anthocyanin composition.